Large viscous boundary layers for noncharacteristic nonlinear hyperbolic problems - Métivier, Guy (Memoirs of the American Mathematical Society, 2005)
Introduction Linear stability: the model case Pieces of paradifferential calculus $L^2$ and conormal estimates near the boundary Linear stability Nonlinear stability Appendix A. Kreiss symmetrizers Appendix B. Para-differential calculus Appendix Bibliography.